Proposals for Improving Legal Regulation of the Institute of Authorized Economic Operator - A. Yu. Komelova (Управленческое консультирование)
The article discusses current issues related to the development of the institution of an authorized economic operator (hereinafter — AEO) in Russia. The study is devoted to the analysis of the regulatory framework, and also analyzes the current state of affairs. the purpose of the article is to identify problems that require discussion and deeper research in order to improve the regulation of the AEO institution; formulating conceptual proposals for its development and involving in this institute companies that really need simplifications when carrying out customs operations for conducting foreign trade activities. This study is based on the methodological approaches of domestic scientists to the problems of development of economic institutions. When conducting the study, the method of comparative analysis of legislation regulating the AEO institution was used; An analysis of scientific literature and existing data from open AEO Registers was carried out. Methods of scientific knowledge, system analysis (deduction, induction, analysis, synthesis), graphic and statistical methods, systems approach were used; methods of monographic, statistical and comparative analysis, generalization and interviews were used. results and scientific novelty of the study. The work focuses on the study of the terms underlying the AEO institution. According to the author, the term should more accurately reflect the purpose and essence of its creation. The legal regulation of the AEO institution requires a new rethinking, with prospects for the development of the institution, as laid down in the standards of the World Customs Organization, from the understanding of AEOs as national companies that have a number of simplifications when performing customs operations, to the understanding of AEOs as organizations — links in the supply chain of products between AEOs of other countries, provided they all meet trade and safety standards. A set of proposals for the development of the AEO Institute has been formed. Conclusions. The proposals concern clarification of terminology and proposals for improving the regulatory framework, in particular the development of simplifications. The federal customs services of the EAEU countries may use the provisions of this article when developing legal regulation for the development of the AEO institution. The degree of elaboration varies from a conceptual idea to the proposal of specific amendments to articles of laws.